Sweet potato (Ipomoea batatas l.) leaves ethanol extract increases endogenous antioxidant activities in hyperlipidemic rats - Mahfudh, Nurkhasanah; Sulistyani, Nanik; Khoirot, Asilah Fatihatul; Tsanawiyah Indah Safira; Othman, Fezah; Zakaria, Zainul Amiruddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Consumption of high-fat foods can induce the formation of free radicals and trigger oxidative stress. The leave of sweet potato (Ipomoea batatas L.) has been reported to be a potent antioxidant in vitro. This study investigates the effect of ethanol extract of purple sweet potato leaves on the endogenous antioxidant activity in hyperlipidemic rats. The sweet potato leaves were oven-dried and extracted using 70% ethanol in a ratio of 1:7 w/v for 24 h, followed by vacuum evaporation. The five groups of test animals were created: normal control-which was given a standard diet, negative control (high-fat diet (HFD) for 14 days), and three treated groups which treated with HFD for 14 days and start for the same time treated with sweet potato leaves extract (SPLE) at the doses of 100, 200, and 400 mg/kg BW for 28 days. The antioxidant activity was measured from liver homogenate on the 29th day. Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) activities, and malondialdehyde (MDA) levels were quantified using spectrophotometry. The high-performance liquid chromatography (HPLC) analysis found rutin as a major chemical content of the SPLE. HFD significantly (p<0.05) decreased the activity of endogenous antioxidants (SOD, CAT, and GSH-Px) and increased the MDA level significantly (p<0.05) compared with the normal group. On the contrary, the treatment with the SPLE significantly (p<0.05) increased the activity of SOD, CAT, and GSH-Px and lowered MDA levels significantly (p<0.05) in a dose-dependent manner compared to the negative control. SPLE increase the activities of endogenous enzymatic antioxidants in hyperlipidemic rats.